The Construction of Expatriate Identity: A Critical Discourse Analysis on “Indonesia Expat” Magazine - Vivian Graciela Chertian; Esther Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2020)
This thesis is a study on the construction of expatriate’s identity in Indonesia Expat magazine. The purpose of this study is to find how the expatriate’s identity is constructed in Indonesia Expat. In this study, the theory used was van Dijk’s (2015) critical discourse analysis. The data were parts of texts taken from Meet the Expat and Info for Expat columns in Indonesia Expat magazine. The writers took a descriptive qualitative approach in this study. According to the findings, there were five identities constructed about the expatriates: skillful, successful, wealthy, healthy, and caring. These identities were constructed by utilizing background, details, graphics, and word choice to generate particular interpretations.Keywords: Critical discourse analysis, expatriate, identity, elite